2015
DOI: 10.1287/inte.2014.0785
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Network Designs for the World’s Largest Broadband Project

Abstract: The national broadband network (NBN) is the largest public infrastructure project undertaken in Australia, and NBN Co is the government-owned company responsible for building the network. By using operations research, NBN Co expects to avoid more than $AUD1.7 billion in unnecessary construction and design costs on this $AUD36 billion project. At the beginning of this 10-year project, NBN Co divided the country into more than 3,000 fiber-serving-area modules (FSAMs), each covering approximately 2,500 premises, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For example, the environmental project (Eijgenraam et al, 2014) reported the highest savings of 7.8 billion euros. Some projects are implemented in multiple companies (Humair et al, 2013) or multiple years (Hu et al, 2015), meanwhile others are single shots projects (Ferris et al 2015, Bunomo et al 2013.…”
mentioning
confidence: 99%
“…For example, the environmental project (Eijgenraam et al, 2014) reported the highest savings of 7.8 billion euros. Some projects are implemented in multiple companies (Humair et al, 2013) or multiple years (Hu et al, 2015), meanwhile others are single shots projects (Ferris et al 2015, Bunomo et al 2013.…”
mentioning
confidence: 99%